Cost and Time Comparison Analysis on Waterproof Material Aluminium Foil and Combination Cement Board and Asphalt Membrane in Roof Construction - Yopi Luthfiansyah; Achmad Alwan Damanik (Journal of World Conference (JWC), 2021)
Existence consumer complaints regarding the quality of the building, especially related to the problem of leakage on the roof during the rainy season, made PT. Toyota Housing Indonesia improvised waterproof material in the underlayer position from conventional waterproofing (aluminum foil) to waterproofing a combination of cement board and asphalt membrane. Therefore the author will analyze the effectiveness of the two materials to overcome the problem of leakage that often occurs in roof construction.This study aims to implement the creation of "zero complaints", and be able to reduce the number of consumer complaints, especially in leaks. As well as to find out the quality of the quality and costs that need to be incurred by the owner related to changes in the type of material to be used in the Housing Project Image of Garden Castle. The method used in this research is using qualitative methods, namely research that is descriptive and tends to using analysis. This research was conducted by collecting data according to conditions in the field by means of observations, project technical data, discussions and interviews with parties involved in the project. It can be concluded that the use of a combination of cement board and asphalt membrane material is more effective in overcoming leakage. And for the cost of waterproofing work on 9 roof units using a combination of cement board and asphalt membrane, it costs Rp.254,067,200 while using aluminum foil material costs Rp.232,011,800, so the use of a combination of cement board and asphalt membrane is more expensive. Rp.22,055,400. The time needed to complete the waterproofing work on 9 roofs measuring 38.8 m2/unit using a combination of cement board and asphalt membrane material is also 2 days longer than the use of aluminum foil material which only takes 14 days.